Pemberdayaan Masyarakat Melalui Pendidikan Biologi Untuk Menjaga Keanekaragaman Hayati dan Keseimbangan Ekosistem - Liza Choirun Nisa; Rahmad Rafid; Rizky Perdana Bayu Putra; Muhammad Fariq Heemal Attruk (Indonesian Journal Publisher, 2024)
Biodiversity is an integral part of the balance of ecosystems that support the survival of various living beings on Earth, including humans. However, threats to biodiversity due to environmental degradation, climate change, and overexploitation have led to significant declines in many species and ecosystems. One effective strategy to address this problem is community empowerment through biology education. Through Biology Education, people can acquire the knowledge and skills necessary to understand the importance of biodiversity conservation as well as the ways in which they can maintain the balance of ecosystems. This study aims to examine how biology education can empower the community in an effort to maintain biodiversity and ecosystem balance. Through a qualitative approach, this study explores the influence of biology education programs on increasing environmental awareness, behavior change, and community involvement in conservation activities. The results showed that biology education can improve people's understanding of the relationship between human activities and their impact on ecosystems. This education Program also encourages communities to engage in various conservation activities, such as afforestation, waste management, and protection of local species.